2014
DOI: 10.1038/srep07190
|View full text |Cite|
|
Sign up to set email alerts
|

Regulation of synaptic plasticity and cognition by SUMO in normal physiology and Alzheimer's disease

Abstract: Learning and memory and the underlying cellular correlate, long-term synaptic plasticity, involve regulation by posttranslational modifications (PTMs). Here we demonstrate that conjugation with the small ubiquitin-like modifier (SUMO) is a novel PTM required for normal synaptic and cognitive functioning. Acute inhibition of SUMOylation impairs long-term potentiation (LTP) and hippocampal-dependent learning. Since Alzheimer's disease (AD) prominently features both synaptic and PTM dysregulation, we investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 81 publications
4
77
1
Order By: Relevance
“…Measuring USVs is widely carried out in genetic ASD model mice (63), with phenotypes observed in models of Foxp1 (64), Cntnap2 (52), Tsc1 (20), Tsc2 (65), Nlgn3 (66), Nlgn4 (67), Shank1 (68), Shank2 (69), Shank3 (70) and Mecp2 (71). In support of our behavioral results, two recent studies have demonstrated that sumoylation in hippocampus can modify mammalian cognitive behaviors by altering hippocampal-dependent learning and memory by Ubc9, a E2 conjugating enzyme (72), and spatial memory by sumoylation of CREB (73). In addition, neuron-specific knockdown of all SUMO-1/2/3 in RNAi transgenic mice leads to anxiety-like behavior, and impairs episodic and fear memories (74).…”
Section: Discussionsupporting
confidence: 88%
“…Measuring USVs is widely carried out in genetic ASD model mice (63), with phenotypes observed in models of Foxp1 (64), Cntnap2 (52), Tsc1 (20), Tsc2 (65), Nlgn3 (66), Nlgn4 (67), Shank1 (68), Shank2 (69), Shank3 (70) and Mecp2 (71). In support of our behavioral results, two recent studies have demonstrated that sumoylation in hippocampus can modify mammalian cognitive behaviors by altering hippocampal-dependent learning and memory by Ubc9, a E2 conjugating enzyme (72), and spatial memory by sumoylation of CREB (73). In addition, neuron-specific knockdown of all SUMO-1/2/3 in RNAi transgenic mice leads to anxiety-like behavior, and impairs episodic and fear memories (74).…”
Section: Discussionsupporting
confidence: 88%
“…Based on various AD mouse models, several studies indicated changes in global levels of SUMO1 conjugates during amyloid pathology (Lee et al., 2014; Marcelli et al., 2017; McMillan, Brown, Henley & Cimarosti, 2011; Nistico et al., 2014). Accordingly, we tested whether these findings can be recapitulated in our His 6 ‐HA‐SUMO1::5XFAD model by making use of the HA tag for high‐affinity detection of SUMO1 conjugates.…”
Section: Resultsmentioning
confidence: 99%
“…Variation in global SUMO1 levels in the context of increased amyloid burden was reported in different AD mouse models (Lee et al., 2014; McMillan et al., 2011; Nistico et al., 2014). For instance, in young (3–6 months old) Tg2576 animals, SUMO1 conjugate levels in hippocampal and cortical tissues were found to be increased, while SUMO1 levels at later stage (17 months old) were comparable to those of age‐matched control animals (Marcelli et al., 2017; McMillan et al., 2011; Nistico et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nicastrin is required for the assembly of presenilin complexes to mediate Notch signalling and for processing and trafficking of β-amyloid precursor protein and thus plays a role in amyloid plaque formation [46]. Proper signalling between presenilin and nicastrin is important not only for processing of APP and accumulation of Aβ peptides but also for synaptic plasticity [47]. The next component of γ-secretase complex is PEN-2, a membrane protein with two predicted transmembrane domains, both N′ and C′ terminals are in extracellular space and with hydrophilic cytosolic loop [48].…”
Section: The γ-Secretase Complex Partnersmentioning
confidence: 99%